TOWARDS SUSTAINABLE COMPANY GROWTH: CONTRIBUTION OF MARKETING IDEAS CONTEST TO FINANCIAL PERFORMANCE BY CONSIDERING CONTEST DESIGN AND MARKETING RESOURCE FACTORS - Fatmasari, Raden Roro; Padma Hanuun, Nazhira Nindya; Yolistina , Anggun (KRIEZ ACADEMY : Journal of development and community service, 2024)
This research investigates the role of marketing ideas contests in driving sustainable corporate growth, with a focus on contribution to financial performance. By considering contest design and marketing resource factors, this research investigates the extent to which idea pool contests can be a catalyst for growth-supporting innovation and employee participation. The results of the analysis show that clear and transparent contest design, together with efficient management of the promotional budget, information technology, and personnel, has a positive impact on the implementation of marketing ideas and, ultimately, the company's financial performance. Inclusive and flexible design supports a diversity of ideas, while wise allocation of resources ensures sustainability of marketing strategies. These findings provide deep insight into the importance of good integration between contest concepts, focused design, and smart resource management to achieve sustainable company growth.